2013
DOI: 10.1111/ced.12057
|View full text |Cite
|
Sign up to set email alerts
|

Hypopigmented keratosis: is it a hyperkeratotic variant of idiopathic guttate hypomelanosis?

Abstract: We have occasionally seen patients with acquired well-demarcated, scattered hypopigmented papules. In this study, we investigated the clinical and histopathological characteristics of such lesions. Biopsies were taken from the lesional and perilesional normal skin from 10 of 13 patients, which were compared with 10 idiopathic guttate hypomelanosis (IGH) samples. The lesions were scattered, well-circumscribed, flat-topped, hypopigmented papules. There was no age or gender predilection. Marked hyperkeratosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Hypopigmented PUVA keratosis is another differential, which is photo-induced, but the lesions are elevated papules rather than macules. 3 Although these lesions have been reported before as IGH-like 2 macules, in view of the characteristic dermoscopic features of amoeboid, petaloid, and feathery margins, we opine that these may actually be IGH rather than IGH-like macules. 4 The proposed pathogenesis of IGH is multifactorial and implicates photodamage.…”
Section: Sirmentioning
confidence: 61%
See 1 more Smart Citation
“…Hypopigmented PUVA keratosis is another differential, which is photo-induced, but the lesions are elevated papules rather than macules. 3 Although these lesions have been reported before as IGH-like 2 macules, in view of the characteristic dermoscopic features of amoeboid, petaloid, and feathery margins, we opine that these may actually be IGH rather than IGH-like macules. 4 The proposed pathogenesis of IGH is multifactorial and implicates photodamage.…”
Section: Sirmentioning
confidence: 61%
“…1,2,6 A subset of both conditions may show some hyperkeratosis, which when significant may result in clinically raised lesions of hypopigmented keratosis, an entity that probably represents the raised hyperkeratotic variant of IGH. 1,3,6 Some patients of both conditions also show epidermal atrophy and flattening of rete ridges. 1,6 Interestingly, the focal or patchy presence of melanin, described by Falabella et al in leucoderma punctata in 1988, is now a known feature of IGH, described as skip areas.…”
Section: Observation Lettermentioning
confidence: 99%
“…In the study reported by Kim et al, 13 cases of HK were reported and 4 of them had a disseminated distribution [ 2 ]. The authors suggested that HK may be a “hyperkeratotic” variant of idiopathic guttate hypomelanosis [ 2 ]. The lesions are distributed more intensively and extensively in our patient compared to previous reported cases.…”
Section: Discussionmentioning
confidence: 99%
“…A few treatment modalities were tried for the HK in the previous reports including tretinoin, propylene glycol, salicylic acid gel, and cryosurgery without significant improvement [ 1 , 2 ]. One exception is that tretinoin gel and salicylic acid ointment provided marked improvement in the case of the localized HK reported by Kokturk et al [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation